An epidemiological study of head injuries in a UK population attending an emergency department. Issue 5 (7th February 2006) - Yates, P J; Williams, W H; Harris, A; Round, A; Jenkins, R
Abstract : We aimed to identify the attendance rate for all head injuries, and for moderate to severe head injury (MSHI), in an emergency department (ED), and related risk factors for MSHI, including age, sex, area of residence, and socioeconomic status (SES). This was a retrospective descriptive epidemiological study of an ED database of head injury attendances over 6 years, carried out in an ED that serves both urban and mixed rural and urban areas, with a wide socioeconomic range, and a total population of 344 600. The main outcome measure was rates of attendance for head injury. Head injury presentations accounted for 3.4% of all attendances per year. An overall rate of 453 per 100 000 was found for all head injuries, of which 40 per 100 000 were moderate to severe (10.9%). Urban residents had significantly greater risk of presenting with MSHI compared with residents of mixed/rural areas. Males were more at risk than females, and children and adolescents had higher risk of MSHI. A high attendance rate of MSHI was found in the <5 year old age group in urban areas for both sexes. A gradient, with higher attendance in groups with lower SES, was observed for children in urban areas, while the gradient was reversed in mixed/rural areas. Head injuries are a relatively common cause of attendance at ED. There is significant variation in attendance with MSHI with regard to sex, age, socioeconomic factors, and type of area of residence. The planning and delivery of preventative and management services may be improved by such analyses.